A Falconer's Ritual: A study of the cognitive and spiritual dimensions of pre-Christian Scandinavian falconry - Bellamy-Dagneau, Karyn, 1986- (2015)
Working from the premise that falconry was introduced in Scandinavia from an eastern origin sometime in the course of the 6th century AD, this paper suggests that the practice may have harboured cognitive and spirituals dimensions unshared by the rest of the feudal, Christian European kingdoms. Falconry is thus reinterpreted in light of an inherited prehistoric human-animal relationship in Scandinavia, in addition to a reconstructed Viking Age cosmology. The multidisciplinary approach of this paper permits us to suggest that falconry was shaped by the culture already in place around 500 AD and that, in turn, it influenced its subsequent development into the Viking Age. The unique relationship between a falconer and a bird of prey may have been the inspiration to the development of the avian hybridity motif of Scandinavian animal art. It may also be likened to the numerous Norse concepts of animalistic souls and shamanistic shape shifting, such as the myths have preserved in memorable images and situations. Rannsóknin gengur út frá því að fálkar hafi þekkst á Norðurlöndum og komið úr austri á 6. öld, og þar er sett fram sú tilgáta að tamning fálka hafi falið í sér andlega þætti sem ekki þekktust í öðrum kristnum evrópskum konungsríkjum á lénstímabilinu. Þannig er fálkatamning endurtúlkuð í ljósi norrænnar arfleiðfar um samband manns og dýrs eins og hún kemur fram í endurgerðri heimsmynd víkingaaldar. Þverfagleg nálgun rannsóknarinnar bendir okkur til þess að fálkatamning hafi mótast menningarlega þegar um 500 e. kr. og hafi síðan mótast af menningunni til víkingaaldar. Einstakt samband fálkatemjara og ránfuglsins gæti haft sín áhrif á þróun hamskiptaminnisins þar sem fuglar koma mjög við sögu, bæði í norrænni dýralist og síðar í goðsögunum þar sem bæði má sjá minni um tengsl sálar og dýrs og hamskipti galdramanna.